Pengaruh Konformitas terhadap Perilaku Konsumtif pada Mahasiswa Konsumen Coffee Shop di Kota Padang - Harlizah, Husnul; Nio, Suci Rahma (Lembaga Yasin AlSys, 2024)
This study aims to see the influence of conformity on consumer behavior among student coffee shop consumers in Padang City. This research uses quantitative methods. The population in this study were students as coffee shop consumers in Padang City with a sampling technique using purposive sampling. The sample in this study amounted to 105 people. The instruments used in this study were the conformity scale and the consumer behavior scale. The results of the analysis using simple linear regression with a significance of p = 0.018 (p <0.05), correlation (R) of 0.231 and the coefficient of determination (R Square) of 0.053. This means that conformity has a significant positive influence on consumer behavior with an influence of 5.3%.